2021
DOI: 10.3389/fonc.2021.697534
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Analysis of the Expression and Prognosis for FKBP Gene Family in Renal Cancer

Abstract: BackgroundThe FK506-binding protein (FKBP) is a family of intracellular receptors that can bind specifically to the immunosuppressant FK506 and rapamycin. Although FKBPs play crucial roles in biological processes and carcinogenesis, their prognostic value and molecular mechanism in clear cell renal cell carcinoma (ccRCC) remain unclear.MethodsUsing pan-cancer data from The Cancer Genome Atlas (TCGA) and public databases, we analyzed the expression and correlation of FKBPs in 33 tumor types. Survival and Cox re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Whereas FKBP11 has not been reported in phagocytosis, immunosuppression of FK506 is vastly applied clinically in organ transplantation ( 44 ). Notably, an in-silico study using datasets overlapping ours also showed a similar prognostic role of FKFB11 in ccRCC ( 45 ). Neither MS4A14 nor KDELR3 was reported related to phagocytosis, and the genes are functionally distant from ADCP in previous studies.…”
Section: Discussionsupporting
confidence: 68%
“…Whereas FKBP11 has not been reported in phagocytosis, immunosuppression of FK506 is vastly applied clinically in organ transplantation ( 44 ). Notably, an in-silico study using datasets overlapping ours also showed a similar prognostic role of FKFB11 in ccRCC ( 45 ). Neither MS4A14 nor KDELR3 was reported related to phagocytosis, and the genes are functionally distant from ADCP in previous studies.…”
Section: Discussionsupporting
confidence: 68%
“…FKBP11 belongs to the superfamily of FK-506 binding protein and is located on chromosome 12q13.12 with 8 exons. Studies have shown that FKBP11 is upregulated in melanoma, hepatocellular carcinoma, and renal carcinoma (28)(29)(30). Mechanistic studies have revealed that FKBP11 promotes cell proliferation and tumorigenesis via protein 53-related pathways in oral squamous cell carcinoma (31).…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely reported that fibroblast FKBP10 is expressed at a higher level in idiopathic pulmonary fibrosis tissue compared with normal lung tissue, while knockdown of FKBP10 can reduce the synthesis of collagen and reduce the migration of fibroblasts [21]. Also, some studies have found higher expression levels of FKBP10 in CcRCC tissues than in normal tissues [22]. In addition, it has been found that FKBP10 can be used as a new biomarker for bioinformatics analysis and in vitro experiments of gastric cancer prognosis and lymphatic metastasis [18].…”
Section: Discussionmentioning
confidence: 99%